Influence of entrepreneurial orientation and absorptive capacities in export performance - Alexandra Silva França; Orlando Lima Rua (Tourism & Management Studies, 2016)
The main purpose of this study is to analyze the influence that entrepreneurial orientation and absorptive capacity have on export performance of small and medium-sized footwear companies. Therefore, this research adopted a quantitative methodological approach, conducting a descriptive, exploratory and transversal empirical study, having applied a questionnaire to a sample of Portuguese companies exporting footwear. From this study it was possible to conclude that entrepreneurial orientation and absorptive capacity enhance export performance of Portuguese footwear companies in foreign markets. It also underline the contribution of this study to the theory of strategic management, since it is known that it encompasses deliberate and emerging initiatives, including the use of resources and capabilities to improve business performance. This study presents entrepreneurial orientation and absorptive capacity as strategic determinants which contribute positively to the export performance